Grain Yield Stability of Maize (Zea mays L.) Hybrids using Ammi Model and GGE Biplot Analysis - Shrestha, J; Subedi, S; Acharya, R; Sharma, S; Subedi, M (SAARC Journal of Agriculture, 2022)
Six maize hybrids; Khumal Hybrid-2, KML-5(A) × KYM-33, KML-8(A) × KYM-33, KWM-91 × KWM-93, KWM-92 × KWM-93, Super-951 were evaluated in a randomized complete block design (RCBD) with three replications at Bhotechaur (Sindhupalchowk), Mandan Deupur (Kavrepalachowk), and Khumaltar (Lalitpur), Nepal to identify stable and superior hybrids. Hybrids were found significant (p<0.01) for grain yield. The effects of environment and genotype × environment (G × E) interactions on grain yield were found to be significant (p<0.01). The combined analysis showed that KWM-91 × KWM-93 produced the highest grain yield (8.89 t ha-1) across all locations, followed by KWM-92 × KWM-93 (8.60 t ha-1), which was at par with each other. The hybrids; KWM-92 × KWM-93 (bi=0.84, CV=18.54%, SD=1.59) and KWM-91 × KWM-93 (bi=1.16, CV=22.37 %, SD=1.99) were found to be more stable, with regression coefficient (bi) nearly equal to unity (1) and grain yields above the grand mean yield. The GGE biplot revealed that KWM-91 × KWM-93 was the most responsive hybrid for Mandandeupur and Bhotechaur environments; whereas, KWM-92 × KWM-93 was for the Khumaltar environment. Hybrid KWM-91 × KWM-93 was the most stably yielding hybrid among all hybrids. This study suggests that KWM-91 × KWM-93 can be promoted for cultivation in mid hills of Nepal. SAARC J. Agric., 19(2): 107-121 (2021)